2020
DOI: 10.1111/jocd.13507
|View full text |Cite
|
Sign up to set email alerts
|

Review on perfume and present status of its associated allergens

Abstract: Background Perfume is basically a cosmetic product applied to human body for an amusing scent or the feeling of freshness. A certain amount of perfume penetrates and remains attached to the protein of the skin when perfume is applied on the body. It evokes a surge of events in human immune system which results with allergic symptoms. Fragrance ingredients are leading cause that can be responsible for the occurrence of allergic contact dermatitis that is recently studied under cosmetic adverse reaction. Aim The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…Fragrance sensitivity is a health condition characterized by the experience of adverse health effects from exposure to a fragranced product [1]. Most commonly reported fragrance reactions include skin, respiratory, neurological, and nasal symptoms [2]. Perfumes have been reported as one of the fragranced products that contribute to fragrance sensitivity in several international studies [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fragrance sensitivity is a health condition characterized by the experience of adverse health effects from exposure to a fragranced product [1]. Most commonly reported fragrance reactions include skin, respiratory, neurological, and nasal symptoms [2]. Perfumes have been reported as one of the fragranced products that contribute to fragrance sensitivity in several international studies [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, 50.6% of the participants of a study reported at least one adverse reaction from cosmetic products, including perfumes [5]. Fragrance substances added to cosmetic products and perfumes contributed to the majority of health adverse reactions caused by fragranced products [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Essential oils are valuable molecules, used in pharmacology because they have a specific effect on other organisms (Tohidi et al, 2019). In cosmetology (Chaudhuri et al, 2020), they are used as a base for the manufacture of perfume and dermatological products (Kumar et al, 2020). In the food industry they are used to enhance the taste, flavour and colour of food and its conservation.…”
Section: Introductionmentioning
confidence: 99%